Labelling, Packaging dan Digitalisasi Pemasaran pada Umkm di Madiun pada Keripik Tahu Walik - Hari Purwanto; Apriyanti; Heny Sidanti; Hendra Setiawan Hendra Setiawan; Ayu Setya Sujianti (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
MSME Kripik Tahu Barokah which has its own taste in the hearts of the people of Banjarejo Madiun has a different taste. The purpose of empowering SMEs is in the field of marketing such as labeling, packaging and marketing of tofu chips where the marketing has not been through online media, but is still offline and delivered to shops, angkringan and stalls. Where the marketing of this tofu walik product is still offline and is constrained by the money from the sale. With marketing training using social media technology as a forum for disseminating information in the era of internet advancement. The training program provided uses lecture, demonstration, socialization, and discussion methods. These implementation activities include planning, implementation and evaluation. The results of the training program showed that the SMEs of Tahu walik chips already understood marketing using social media technology ranging from products, packaging, product photos, information and posting. The expected impact of the training program is awareness of the role of marketing technology media, such as social media, which can be utilized and maximized to increase sales so that later it can be known and known by the wider community.